Visible Light-Responsive Photocatalytic Activity of Boron Nitride Incorporated Composites - Wang, Ning; Yang, Guang; Wang, Haixu; Sun, Rong; Wong, Ching-Ping (Frontiers in Chemistry, 2018)
Photocatalysts are essential to promote the highly efficient applications of solar energy in water splitting and/or the degradation of organic contaminations. Especially, the visible light-responsive photocatalysts could benefit with the cost-effective splitting or degradation due to the unlimited sunlight and the absence of expensive light emitter. In the photocatalysts, the charge transfer rates as well as the hole-electron recombination rate are two critical factors that determine the photocatalytic activity, which could also be affected by the dimension, defects, doping and morphologies controlled by the synthesis methods. Boron nitride (BN) is an ultrawide-bandgap semiconductor, and the combination of BN with the visible light-responsive photocatalysts has been found to be effective in enhancing the photocatalytic activities. Therefore, it should be meaningful to understand the BN incorporated photocatalytic composites in depth, including the synthetic approaches, the activity improving mechanisms and the versatile applications. In this review, we mainly focused on the assembly method of BN incorporated photocatalysts; the activity enhancing mechanism by introducing the BN in the photocatalytic composites as well as the properties and the applications. In the end, we gave a conclusion and an outlook for the BN incorporated photocatalytic composites.